Low dose of bisphenol A impairs the reproductive axis of prepuberal male rats - Gámez, Juan Manuel (2014)
The objective of the present work was to study the effect of a low dose of bisphenol A (BPA), on the reproductive axis of prepuberal male rats exposed to the endocrine disruptor (ED) during gestation and lactation period. Wistar-mated rats were treated with either 0.1 % ethanol or BPA in their drinking water until their offspring were weaned at the age of 21 days. The estimated average dose of exposure to dams was approximately 3 μg/kg/day of BPA. The pups were sacrificed on the 35th day of life. Body weight was measured during the development and at the moment of the sacrifice; testicular and seminal vesicles weight and their respective relative weights were also measured. LH, FSH and testosterone were determined and histological studies of testicular tissue were also performed. Body weight at the moment of the sacrifice was significantly higher in the group exposed to BPA; testicular weight decreased significantly; seminal vesicles weight and relative weights of testes and seminal vesicles were not modified by treatment. LH and FSH serum levels increased significantly after treatment, meanwhile testosterone showed no significant changes. Histological studies showed the lumen of seminal tubes reduced by the presence of immature cells of the spermatic lineage. Our results suggest that pre- and early postnatal exposure to a low dose of BPA disrupts the normal function of the reproductive axis in prepuberal male rats. The effects of the ED may be exerted at different levels of the axis and may be dependent on the dose, manner of administration, and the moment of exposure to the disruptor.